2021
DOI: 10.1111/bph.15641
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P2Y12 receptors in a nitroglycerin‐induced model of migraine in male mice

Abstract: Supporting information: 5 Figures, 2 Tables and methods Authors contributions: FG carried out behaviour, IHC, FACS experiments, analysed data, performed statistical analyses, and drafted the manuscript. MB conducted HPLC analysis, AI and LH performed blood pressure and heart rate measurement, and analysed the data. LO carried out confocal microscopy and revised the manuscript. ZB designed experiments and revised the manuscript. BS designed and supervised the study and finalized the paper. All authors read and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 92 publications
(169 reference statements)
0
1
0
Order By: Relevance
“…Previous studies showed that activation of P2Y12R in SGCs of TG was in involved in orofacial neuropathic pain induced by unilateral lingual nerve injury ( Katagiri et al, 2012 ; Sugawara et al, 2017 ). In addition, microglia P2Y12R in STN was also verified to be involved in several types of orofacial pain, including migraine and tongue cancer pain ( Tamagawa et al, 2016 ; Gölöncsér et al, 2021 ). In our studies, P2ry12 was expressed not only in SGCs, but also in macrophages and MLCs, suggesting that the pro-nociceptive effect of P2Y12R may not only rely on the glia-neuron interactions but also on the neuroimmune communication.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed that activation of P2Y12R in SGCs of TG was in involved in orofacial neuropathic pain induced by unilateral lingual nerve injury ( Katagiri et al, 2012 ; Sugawara et al, 2017 ). In addition, microglia P2Y12R in STN was also verified to be involved in several types of orofacial pain, including migraine and tongue cancer pain ( Tamagawa et al, 2016 ; Gölöncsér et al, 2021 ). In our studies, P2ry12 was expressed not only in SGCs, but also in macrophages and MLCs, suggesting that the pro-nociceptive effect of P2Y12R may not only rely on the glia-neuron interactions but also on the neuroimmune communication.…”
Section: Discussionmentioning
confidence: 95%
“…NTG activates and sensitizes the trigeminal system [107,108], central mechanism crucial in migraine pathophysiology, as described earlier. In a recent study, it was shown that inhibition of P2Y12 receptors with the selective antagonist PSB-0739 decreases c-Fos expression in the NTG model of migraine pain in mice [109], which underlines the possible role of P2Y receptors in migraine pathomechanism.…”
Section: Purinerg Systemmentioning
confidence: 96%
“…Mice were assigned randomly to 7 groups and intragastrically administrated with a single dose of vehicle, isaridin E (12.5, 25, 50, or 100 mg/kg), or clopidogrel (10 mg/kg) at 3 h before the cutting-tail experiment [42,43]. Tails were transected at a distal margin of 5 mm and were immediately immersed into 10 mL of saline at 37 • C. The bleeding time was recorded as when the observed bleeding ceased.…”
Section: Tail-bleeding Assaymentioning
confidence: 99%